Development of Canva-Based SUKA SASA Interactive Multimedia to Improve Elementary School Early Reading and Numeracy Skills - Wijayanto, Zainnur; Rochmiyati, Siti; Hidayat, Rosidah Alim; Asmi, Yuni Karsih (Jurnal Pendidikan Progresif, 2025)
Development of Canva-Based SUKA SASA Interactive Multimedia to Improve Elementary School Early Reading and Numeracy Skills. Technological developments encourage innovations in learning media that can facilitate the delivery of material and create more engaging learning experiences. This study aims to describe the results of the analysis of teachers’ and students’ needs, as well as to test the feasibility and effectiveness of Canva-based SUKA SASA interactive multimedia in improving the early reading and numeracy skills of first-grade elementary school students. The research employed a research and development (R&D) approach using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The study involved 65 first-grade elementary school students in Karanganyar Regency selected by purposive sampling. Data collection techniques included interviews, observations, and learning outcome tests on early reading and foundational numeracy skills. The data were analyzed quantitatively using descriptive statistics and inferential testing, and were also supported by qualitative analysis. The findings show that the developed Canva-based SUKA SASA multimedia is valid, feasible, and effective in improving both early reading and foundational numeracy skills. The media's feasibility was supported by expert assessments: media experts (80.60%), material experts (95.40%), practitioner experts (95.40%), and positive student responses (84.38%), all of which indicate that the media is classified as very feasible. The effectiveness test yielded a significance value of 0.000, indicating a significant improvement in learning outcomes after using the media. The effect size test result was 1.39, showing a strong impact. Therefore, Canva-based SUKA SASA interactive multimedia is effective in supporting first-grade students' literacy and foundational numeracy skills. The integration of visual and interactive technology, such as Canva, can be an innovative strategy in fostering active, enjoyable, and meaningful learning. Keywords: early reading skills, foundational numeracy skills, interactive multimedia, addie, elementary school.